Russia's Human Capital: Performance and Comparisons - Ivanova, Tatiana A.; Karelina, Mariia G.; Trofimova, Violetta Sh.; Valyaeva, Galina G.; Reent, Natalia A. (International Journal of Economics and Financial Issues, 2015)
Article discusses the results of the valuation of human capital in Russia by analyzing the dynamics of in the period from 2007 to 2012 in nominal and real terms. The changes in the value of human capital by age groups are studied, cross-country differences in the estimates of human capital are revealed. The cost of human capital is estimated via two methods: the cost method proposed by Russian scientist M.M. Kritsliy, and the income method developed by the OECD. Current study reflects on the modified OECD method, which is applicable for statistical information disaggregated by five-year age intervals. Calculations show that in 2012 the total value of the human capital in Russia amounted to 768.7 trillion rubles if counted using M.M. Kritsliy' method and 504.6 trillion rubles using OECD method. In real terms, growth in comparison with 2007 was 40 percent using the first method 10 percent using OECD method. The comparison of the estimates on the value of Russia's human capital by age groups showed that the younger ages are ‘richer' than those in older age groups. Comparison of macro characteristics of the Russian economy showed that the gross stock of human capital at times exceeds the GDP and the stock of physical capital. The study revealed cross-country differences in the cost of and the level of equipment with human capital in Russia and the United States. Keywords: human capital, Russia, dynamics, age groups, cross-country comparisons JEL Classifications: O15; R12